Effect of music on running performance among recreational runners: a scoping review - Zaidi, Raja Nurzafirah Atiqah Raja
Introduction: Music is one of the many mediums that can stimulate the mood, emotion, and improve atmosphere. These days, music is easily accessible through gadgets such as smartphones, MP3 and MP4s, and also through applications such as YouTube and Spotify. Many research has been done on the effect of music on performance among professional athletes. This review aimed to provide a synthesis from previous studies on effect of music on running performance among recreational runners. Methods: A comprehensive search of academic journals on this topic published from 2015 until 2021 was conducted. A total of 9 truly eligible studies were selected from 239 studies screened from electronic databases which included EBSCOhost, ScienceDirect, Scopus, and SpringerLink. Results: Fives studies investigated the effect of music on running cadence. Two studies reported that running cadence in music condition is higher than no music condition. Three studies also reported that running with high tempo music resulted in higher running cadence compared to running cadence in slow tempo music. One study reported that females has higher running cadence compared to males. In addition, there were four studies reported on running speed. Two studies reported that there is no effect in running speed, even though there is music stimulus. However, a study reported there is an effect in running speed in music condition compared to no music condition, and another study reported running speed is higher with high music tempo compared. In addition, a study reported running speed is higher when listening to asynchronous music. A study also reported a faster running behaviour when participants were not instructed to match the tempo of music. Next, two studies reported on step length and running distance. A study reported step length is larger in uninstructed condition while another study reported step length and running distance increases when running to synchronized music. Three studies reported on heart rate, perceived exertion, blood lactate, and total time effort. All study found no difference on heart rate reading in no music condition and with music condition. One study reported on an increment of total time effort in music condition. One study reported an increase in rating of perceived exertion after anaerobic threshold intensity when running in music condition. While two other studies reported a lower rating of perceived exertion when listening to music and listening to synchronized music condition. A study reported on blood lactate and found an increment in blood lactate after anaerobic threshold intensity when running in music condition. Finally, one study reported on arousal and feelings and found that arousal score is higher in music condition, as well as feelings were more positive in music condition.